Determinantes regionais da produtividade industrial: O papel da infraestrutura - Daniela Schettini; Carlos Roberto Azzoni (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper evaluated the role of infrastructure on the productivity of industries in the Brazilian mesoregions. We found that infrastructure positively affects the efficiency of industries, although due to the size of the estimated coefficients, this influence is small. Considering the average levels of efficiency and product, a 1% increase in regional coverage of roads leads to an increase in the regional productive efficiency indicator (which varies between zero and one) around 0.1289 points and 0.121% in the regional industrial product; similar increase in urban infrastructure (consisting of water supply, sanitation and street lighting) leads to an increase in efficiency around 0.2801 points and 0.247% in the product; for the telephony sector, which showed only marginally significant, the result is an increase of 0.152 points in the efficiency indicator and 0.142% in the product.
Keywords: R1; R11; R15; 330; infrastructure; regional efficiency; regional growth